The Influence of Sport and Structured Exercise in Prostate Cancer Management: Recommended Modalities and Narrative Review - Kaczmarek, Julia; Błażuk, Michał; Ejsner, Rafał; Kościółek, Kinga; Grelowska, Aleksandra; Dziewięcka, Oliwia; Ziębka, Wojciech (Quality in Sport, 2026)
Prostate cancer is one of the most common malignancies among men, with a steadily increasing global incidence. Over recent decades, major advances in imaging techniques and therapeutic strategies have significantly improved diagnostic accuracy and survival outcomes. Nevertheless, treatment-related adverse effects remain a substantial clinical challenge and frequently impair patients’ quality of life. This review summarizes current diagnostic approaches and treatment modalities for prostate cancer, with a particular emphasis on the influence of sport and structured exercise recommendations as supportive interventions. Exercise has been shown to improve physical function, reduce fatigue, and enhance quality of life during and after treatment. In the setting of radical prostatectomy, both preoperative and postoperative exercise interventions, particularly pelvic floor muscle training, accelerate functional recovery and reduce urinary incontinence. In patients undergoing androgen deprivation therapy, physical activity, especially resistance training, effectively counteracts treatment-related adverse effects, including loss of muscle mass, increased adiposity, fatigue, and psychological disturbances. Although current evidence regarding the association between physical activity and reduced prostate cancer risk remains inconclusive, emerging data suggest that exercise may positively influence disease progression and survival outcomes. Physical activity should therefore be considered an integral component of comprehensive prostate cancer care. Further studies are required to establish standardized and evidence-based exercise guidelines for this patient population.